2021
DOI: 10.1532/hsf.4279
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Roles of Right Coronary Artery Disease Severity and Systemic Immune Inflammation Index in Predicting Atrial Fibrillation After Coronary Bypass Operations in Patients with Right Coronary Artery Disease

Abstract: Background: Postoperative atrial fibrillation (PoAF) is observed at a rate of 25-40% in the postoperative period after coronary artery bypass graft (CABG) surgery and can increase mortality, morbidity, and treatment costs. Inflammation and coronary artery disease (CAD) severity are important parameters to predict PoAF. Methods: Patients with right coronary artery (RCA) disease who underwent isolated CABG operation between January 1, 2017 and April 15, 2020, were included in the study retrospectively. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…The majority of study participants were male, comprising 35.2%–78.4% of patients. Six studies enrolled patients undergoing CABG ( 14 , 20 , 21 , 29 31 ), whereas one study also included those undergoing other cardiac surgical procedures, including valve replacements ( 22 ). Another study only enrolled patients undergoing mitral valve surgery ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of study participants were male, comprising 35.2%–78.4% of patients. Six studies enrolled patients undergoing CABG ( 14 , 20 , 21 , 29 31 ), whereas one study also included those undergoing other cardiac surgical procedures, including valve replacements ( 22 ). Another study only enrolled patients undergoing mitral valve surgery ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients who developed POAF had significantly higher SII values than those who did not, with a pooled MD of 493.53 (95% CI, 284.83–702.24; p < 0.00001) ( Figure 4 ) ( 19 21 , 29 31 ). The odds of developing POAF were 3.24-fold higher in patients with high SII levels (OR, 3.24; 95% CI, 1.6–6.55; p = 0.001) ( Figure 5 ) ( 14 , 19 , 20 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29] Also, there are recent publications showing that SII is associated with the development of atrial fibrillation (AF) in the postoperative period after coronary artery bypass grafting surgery. 30,31 However, there are no studies comparing inflammatory parameters in predicting the development of malignant ventricular arrhythmia (MVA). The aim of the present study is to investigate the relationship between inflammatory parameters and MVA development in STEMI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these scoring systems, inflammatory parameters obtained from routine blood values are also used to predict the risk of PoAF 17,18 . The most popular of these is the neutrophil/lymphocyte ratio, and the systemic immune inflammation index obtained by the platelet count added to this formula has also been investigated and its predictive value has been shown 19,20 . Ata et al 21 reported in another study that preoperative high BNP levels and advanced age were important predictors for the development of POAF in patients who underwent isolated coronary bypass surgery (CABG) with CPB.…”
mentioning
confidence: 99%